'Feeling at Home Away from Home?' Social Participation of Refugee Students in Cyprus: A Mixed Methods Case Study Design. (29th December 2020) - Trisokka, Lambri; Gautsch, Leslie; Mamas, Christoforos
Abstract: In the context of increasing numbers of refugee students being integrated into the national school system of host countries globally, the necessity of inclusive school environments for these students is growing. Yet schools may not be well prepared and supported to meet the unique needs of refugee students, who may struggle to adjust to their new reality. In this paper, we present the results of a mixed methods case study that explored aspects of the social participation experiences of three Syrian refugee siblings in a public elementary school in Cyprus, as a telling case for the struggles of refugee children to socially participate with their peers in asylum-country public schools. Social network and interview data were collected to examine how effectively the three refugee siblings participate in school life and the factors that may hinder their social participation. The findings are fairly worrisome, as the three refugee siblings were found to maintain a lower social participation status than their non-refugee peers.